Diversity Of Freshwater Fishes In Aceh Province With Emphasis On Several Biological Aspects Of The Depik (Rasbora Tawarensis) An Endemic Species In Lake Laut Tawar - Abidin, Muchilisin Zainal (2010)
Intensive survey of fish biodiversity was conducted for six months in 17 locations covering the five regions of Aceh Province to build a comprehensive database in this area. A total of 711 fishes belonging to 114 species,o 69 genera, 41 families and 12 orders were recorded in this study. Cyprinidae was the predominant freshwater fish group in the Aceh Province. The Lembang River had the highest species richness and diversity index in the Province. Regionally, the diversity index was highest in the northern region. However, the highest species richness was found in the western region. Six species i.e. Puntius brevis, Channa striata, Anguilla bicolor, Anabas testudineus, Clarias teijsmani, and Hampala macrolepidota were the most widely distributed.